2010
DOI: 10.1096/fj.09-150615
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of Wnt signaling mediated by CK1‐phosphorylated DishevelledviaRor2

Abstract: Dishevelled (Dvl) is a multifunctional effector of different Wnt cascades. Both canonical Wnt3a and noncanonical Wnt5a stimulate casein-kinase-1 (CK1) -mediated phosphorylation of Dvl, visualized as electrophoretic mobility shift [phosphorylated and shifted Dvl (ps-Dvl)]. However, the role of this phosphorylation remains obscure. Here we report the functional interaction of ps-Dvl with the receptor tyrosine kinase Ror2, which is an alternative Wnt receptor and is able to inhibit canonical Wnt signaling. We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 38 publications
3
71
0
Order By: Relevance
“…One group reported that phosphorylation of Dvl2 at Thr 206 was necessary for proper orientation of the mitotic spindle (35), and another showed that Dvl2 phosphorylation at Ser 143 and Thr 224 enables binding to polo-like kinase 1 to facilitate primary cilia disassembly (36). Dvl2 phosphorylation mediates binding to Ror2, although the sites of phosphorylation were not determined (37). A recent extensive analysis identified dozens of phosphorylated Ser/Thr residues in Dvl (or the Drosophila ortholog, Dsh).…”
Section: Discussionmentioning
confidence: 99%
“…One group reported that phosphorylation of Dvl2 at Thr 206 was necessary for proper orientation of the mitotic spindle (35), and another showed that Dvl2 phosphorylation at Ser 143 and Thr 224 enables binding to polo-like kinase 1 to facilitate primary cilia disassembly (36). Dvl2 phosphorylation mediates binding to Ror2, although the sites of phosphorylation were not determined (37). A recent extensive analysis identified dozens of phosphorylated Ser/Thr residues in Dvl (or the Drosophila ortholog, Dsh).…”
Section: Discussionmentioning
confidence: 99%
“…Ror2 is known as an alternative Wnt co-receptor mainly for Wnt5a (reviewed in Minami et al, 2010). Wnt5a signaling by means of Ror2 can counteract the canonical Wnt/ b-catenin pathway (Mikels and Nusse, 2006), while protein constructs representing human BDB1 mutations lose this inhibitory effect (Winkel et al, 2008;Witte et al, 2010a). Using the BDB1 mouse model (Ror2 p.W749X), Witte et al (2010b) demonstrated the presence of a DC/PFR in the mouse (see also Fig.…”
Section: Developmental Dynamicsmentioning
confidence: 95%
“…Ror2 elicits multiple functions in Wnt signaling (see also Fig. 1): (1) Ror2 interacts with Frizzled (Fzd) receptors and the intracellular protein Dishevelled (Dvl) to activate Wnt/PCP signaling, 42,43 (2) Ror2 is able to antagonize Wnt/b-Catenin signaling in cells and embryonic tissues, 44,45 and (3) Ror2 activates a PI3K-dependent signaling cascade that transcriptionally regulates expression of paraxial protocadherin (PAPC). 46,47 PAPC and the closely related PCNS are the two paralogs of Protocadherin 8 (PDCH8) in Xenopus laevis.…”
Section: Wnt Signalingmentioning
confidence: 99%